Effect of Eating Habits on Oral Health among Junior High Students in the Cape Coast Metropolis - Gorleku, Philip N.; Setorglo, Jacob; Gorleku, Oxana; Dzefi-Tettey, Klenam; Edzie, Emmanuel K.; Piersson, Albert D.; Antwi, Richard (International Journal of Innovative Research in Medical Science, 2019)
The effect of eating habits on the oral health of 200 students at University Junior High School was assessed using cross-sectional survey. 51.8% of the respondent perceived they have good oral health and 41.7% had never had any dental condition in the last 6 months. However, there was prevalence of 58.2% dental conditions among the respondents. 69.3% had no difficulty brushing the teeth and 56.8% had no difficulty in eating as a result of dental problem. As such, 77% of the respondents never visited the dentist in the past five years. The oral health practices among the respondents were good as 61.4% responded they brush their teeth at least twice a day. The participants generally had bad eating habits as 56.1%, 33.6% and 50%, respectively take fizzy drinks, eat sweets and biscuits with other pastries for more than 3 times in a week. 41.5% had a scores ≤ 15.0 on total eating habit indicating good eating habits and 52.0% had scores ≥16.0, indicating bad eating habits. This accounted for 58.2% having various dental conditions. Therefore, there is the need for an oral health promotion programme to increase awareness of good oral health practices and good eating/snacking habits among the students.